Cover Image, Volume 30, Issue 1. (January 2017) - Zhou, Ziwu; Han, Fei; Rapacchi, Stanislas; Nguyen, Kim‐Lien; Brunengraber, Daniel Z.; Kim, Grace‐Hyun J.; Finn, J. Paul; Hu, Peng
Abstract : The cover image, by PENG HU et al., is based on the Research Article Accelerated ferumoxytol ‐ enhanced 4D multiphase, steady ‐ state imaging with contrast enhancement (MUSIC) cardiovascular MRI : validation in pediatric congenital heart disease, DOI:10.1002/nbm.3663 .